Implications of Islamic Inheritance Law on the Division of Joint Property in Mixed Marriages in Indonesia - Alexadra pierera; justin pastor; selena pacito (Legal Frontier, 2025)
This study examines the implications of Islamic inheritance law on the division of joint property (marital assets) in the context of mixed marriages in Indonesia, where one spouse is Muslim and the other adheres to a different religion. As a country with a plural legal system, Indonesia recognizes Islamic law, civil law, and customary law, each of which may apply differently depending on the personal status of the parties involved. The research explores legal ambiguities and conflicts that arise when Islamic inheritance principles, which are binding for Muslims under Indonesian law, intersect with civil regulations in mixed marriages. Through a doctrinal legal research method supported by case studies and analysis of statutory and judicial interpretations, the study finds that the application of Islamic inheritance law often creates legal uncertainty in determining heirs and the rightful distribution of joint property. Furthermore, the research highlights the necessity for legal reform or clearer regulatory guidance to ensure equity and legal certainty for parties in mixed marriages